2000
DOI: 10.1074/jbc.m001522200
|View full text |Cite
|
Sign up to set email alerts
|

A Functionally Conserved N-terminal Domain of the Friend of GATA-2 (FOG-2) Protein Represses GATA4-Dependent Transcription

Abstract: GATA4 isTaken together, these results define a set of evolutionarily conserved mechanisms by which FOG proteins repress GATA-dependent transcription and thereby form the foundation for genetic studies designed to elucidate the role of FOG-2 in cardiac development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 38 publications
(59 reference statements)
5
115
0
1
Order By: Relevance
“…We have previously shown that multiple zinc fingers domains of FOG-2 are able to physically associate with the N-terminal zinc finger of GATA4 [16]. Since the zinc finger domains of FOG-2 and FOG-2S are identical, we would predict that FOG-2S would be able to bind GATA4.…”
Section: Fog-2s Physically Interacts With Gata4mentioning
confidence: 96%
See 3 more Smart Citations
“…We have previously shown that multiple zinc fingers domains of FOG-2 are able to physically associate with the N-terminal zinc finger of GATA4 [16]. Since the zinc finger domains of FOG-2 and FOG-2S are identical, we would predict that FOG-2S would be able to bind GATA4.…”
Section: Fog-2s Physically Interacts With Gata4mentioning
confidence: 96%
“…This protein is identical to FOG-2 except it lacks the N-terminal 132 amino acids where the FOG repression motif is located (Figure 1). It contains all of the zinc finger motifs, the C-terminal binding protein (CtBP) interaction domain, and the nuclear localization domain previously characterized in FOG-2 [16].…”
Section: Isolation Of An Alternative Transcript Of Murine Fog-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, FOG-1 might endow GATA-1 with corepressor activity. In support of the latter possibility, it has been shown that FOG proteins can associate with members of the carboxyl-terminal binding protein (CtBP) family of corepressors (7,(39)(40)(41)(42), although the relevance of these interactions to erythroid gene expression remains uncertain (43). To distinguish between these two possibilities, we examined occupancy by wild-type and mutant GATA-1-ER protein at the GATA-2 gene.…”
Section: Hs2 (mentioning
confidence: 99%